Ondina Valla, une « championne du fascisme » aux Jeux olympiques de Berlin (1936) - Suzy Toson (Genre & Histoire)
At the 1936 Olympic Games in Berlin, at the age of 20, Trebisonda Valla, nicknamed Ondina, became the first Italian woman to win an Olympic gold medal. This personal endeavor quickly became an unwilling hostage of the Fascist dictatorship which declared it to be a victory of Fascism, thus underlining the political stakes of this event. For the regime’s propaganda, Ondina Valla became a “champion of fascism”. Through the study of this Olympic victory, this article sheds light on the prolific sporting career of this Italian athlete, most of which took place during the Fascist period, enabling an exploration of the Fascist gendered politics that shaped Italian women’s sport over two decades. Above all, by rethinking the 1936 Olympics through Ondina Valla’s own experience, in particular by studying photographs and testimonies from the athlete collected afterwards, this portrait allows us to examine central issues in the study of the relationship between society and totalitarian regimes: the impact of fascist ideology on Ondina Valla’s development and identity, and the way in which she was able to appropriate, in the words of historian Alf Lüdtke, the world shaped by fascist dictatorship.